PENGEMBANGAN MODEL PEMBELAJARAN MY TRIP MY ADVENTURE - Dedy Febry Rachman; Restu Fahdiansyah (SOLID, 2019)
ABSTRACTThe purpose of this development research is expected to produce a product development package in the form of a learning model: 1). Learning device, 2). Assessment / evaluation guide to learning, 3). Guidelines for learning development, 4). Produce game- based learning models adopted from monopoly, 5). The development of the model is based on identifying the characteristics of students at the age that has reached the formal operational stage in terms of cognitive development, 6). The development of the model is based on the identification of learning objectives by considering the curriculum that has been implemented, namely the development of materials from the 2013 curriculum, 7). The learning model focuses on one material namely foreign eXIchange rates, and the same model cannot be applied to other subject matterAfter the product prototype was developed, the eXIpert validation test process, individual trials, small group tests and field tests were carried out. Based on the test results, the learning model is very valid, interesting, and effective can be applied in learning. This can be seen from the results of validation tests with the level of product feasibility of eXIperts content / material of 100%, validation of learning media eXIperts obtained an average score of 97.5%. Level of attractiveness of the product with an average percentage score of 89.76% entered the criteria very interesting. Effective products are used with an average percentage score of 79.66%.This product can also be used for a wider audience with adjustments, especially adjustments to the characteristics of students as users. Furthermore, the learning model that has been developed can be integrated with the use of information and communication technology.Keywords: Development, Learning Model, My Trip My Adventure